A Field Study of Atmospheric Icing Analysis in a Complex Terrain of the High North - Taimur Rashid; Umair N. Mughal; Mohamed Y. Mustafa; Muhammad S. Virk (The International Journal of Ocean and Climate Systems, 2014)
Analyses of atmospheric icing events hold the key for computing the significant parameters leading to icing load calculations. In the cold regions of the high north, atmospheric icing loads on structures become important when it comes to design and safety of infrastructures. Furthermore, icing load calculations over a certain period of time provide a vital input for designers to improve the safety of structures. Patterns of icing events can be evaluated in correlation with other meteorological parameters such as atmospheric temperature, relative humidity and wind speed to better estimate icing loads. A field study has been performed in the complex terrain of northern Norway, by the atmospheric icing research team of Narvik University College, where customized meteorological atmospheric ice monitoring stations were installed to study atmospheric icing events in relation with the associated weather parameters. The meteorological parameters of three different sites in the vicinity of Narvik ( 68°25 ′ 14 ′ N17°33 ′ 36 ′ E ) were collected, sorted, averaged to standardized timeline and further validated with recordings of weathers parameters obtained from the national weather forecasts, where a good agreement was found. Analyses were mainly performed between accreted ice loads and associated meteorological parameters. The results presented can be used as base for the development of more detailed mathematical models for the better prediction of atmospheric icing events in complex terrains.